Effect of vertically oriented few-layer graphene on the wettability and interfacial reactions of the AgCuTi-SiO2f/SiO2 system - Z. Sun (Nature Portfolio, 2017)
Abstract With the aim of expanding their applications, particularly when joining metals, a simple but effective method is reported whereby the surface chemical reactivity of SiO2f/SiO2 (SiO2f/SiO2 stands for silica fibre reinforced silica based composite materials and f is short for fibre) composites with vertically oriented few-layer graphene (VFG, 3–10 atomic layers of graphene vertically oriented to the substrate) can be tailored. VFG was uniformly grown on the surface of a SiO2f/SiO2 composite by using plasma enhanced chemical vapour deposition (PECVD). The wetting experiments were conducted by placing small pieces of AgCuTi alloy foil on SiO2f/SiO2 composites with and without VFG decoration. It was demonstrated that the contact angle dropped from 120° (without VFG decoration) to 50° (with VFG decoration) when the holding time was 10 min. The interfacial reaction layer in SiO2f/SiO2 composites with VFG decoration became continuous without any unfilled gaps compared with the composites without VFG decoration. High-resolution transmission electron microscopy (HRTEM) was employed to investigate the interaction between VFG and Ti from the AgCuTi alloy. The results showed that VFG possessed high chemical reactivity and could easily react with Ti even at room temperature. Finally, a mechanism of how VFG promoted the wetting of the SiO2f/SiO2 composite by the AgCuTi alloy is proposed and thoroughly discussed.